Essential aspects on in vitro fertilization techniques in cattle - Salgado-Cruz, Erika (2020)
In vitro embryo production includes several techniques for the multiplication of genetically superior animal lines under laboratory conditions. To obtain embryos in the laboratory, different protocols and equipment are required to simulate the natural conditions of development of the embryos in the mother, seeking to achieve efficient results. Embryo production consists of three stages, in vitro maturation (IVM) of oocytes, in vitro fertilization (IVF) and in vitro culture (IVC) of possible zygotes, seeking to obtain quality blastocysts for greater reproductive efficiency and genetic improvement of the herds.